2016
DOI: 10.1002/asia.201600695
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Hydrido Iron(II) Compounds with cis‐Reactive Sites: Combination of Iron and Diphosphinodithio Ligand

Abstract: The cationic complex [Fe(P2 S2 )(NCMe)2 ](2+) (P2 S2 =(Ph2 PC6 H4 CH2 S)2 (C2 H4 ) ([1(NCMe)2 ](2+) )), with two MeCN ligands in a cis orientation, was synthesized and characterized. The MeCN ligand in [1(NCMe)2 ](2+) undergoes further substitution by a hydride ligand or CO to give iron(II) hydrides [H1(NCMe)](+) , [H1H](0) , and [H1(CO)](+) . The order of reactivity of the hydrides was [H1H](0) >[H1(NCMe)](+) >[H1(CO)](+) , and was illustrated by their reactions toward protic acids, the organic cation of 10-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Owing to its soft and flexible coordination properties, the phosphine-thioether ligand has been investigated intensively for group 10 metals such as Pd or Pt . In our previous study, we found that the tetradentate ligand (Ph 2 PC 6 H 4 CH 2 S) 2 (C 2 H 4 ), abbreviated as P 2 S 2 , coordinated with iron­(II) to form the cationic complex [(P 2 S 2 )­FeH­(CO)] + folded in such a way that the hydride and CO ligand are in a cis -α disposition . The dicationic complex [Ni­(P 2 S 2 )]­(BF 4 ) 2 ([ 1 ] 2+ ) was prepared by the straightforward treatment of a solution of P 2 S 2 in THF with a solution of Ni­(BF 4 ) 2 ·6H 2 O in isopropanol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to its soft and flexible coordination properties, the phosphine-thioether ligand has been investigated intensively for group 10 metals such as Pd or Pt . In our previous study, we found that the tetradentate ligand (Ph 2 PC 6 H 4 CH 2 S) 2 (C 2 H 4 ), abbreviated as P 2 S 2 , coordinated with iron­(II) to form the cationic complex [(P 2 S 2 )­FeH­(CO)] + folded in such a way that the hydride and CO ligand are in a cis -α disposition . The dicationic complex [Ni­(P 2 S 2 )]­(BF 4 ) 2 ([ 1 ] 2+ ) was prepared by the straightforward treatment of a solution of P 2 S 2 in THF with a solution of Ni­(BF 4 ) 2 ·6H 2 O in isopropanol.…”
Section: Resultsmentioning
confidence: 99%
“…All reagents were purchased from Sigma-Aldrich and used as received. (Ph 2 PC 6 H 4 CH 2 S) 2 (C 2 H 4 ) was prepared according to our previous methods . Et 2 O, pentane, THF (dried by distillation over sodium), MeCN (dried by distillation over CaH 2 ), and CH 2 Cl 2 for general use were of analytical (AR) grade and stored under N 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the backbone of tetraphos to a thioether‐based linkage resulted in a more flexible tetradentate ligand P 2 S 2 (Figure ). The corresponding iron dihydride, which was synthesized from the cationic acetonitrile complex and Bu 4 NBH 4 , was shown to adopt the cis geometry for the hydride ligands …”
Section: Tetradentate Ligand Systemsmentioning
confidence: 99%
“…Cis ‐(P 2 S 2 )FeH 2 was reported to lose H 2 gradually in solution over the time . Protonation of one of the hydride ligands was readily accomplished in MeCN using a weak acid such as a protonated phosphazene, leading to the formation of cis ‐[(P 2 S 2 )FeH(MeCN)] + .…”
Section: Tetradentate Ligand Systemsmentioning
confidence: 99%